Urinary continence outcomes during the transition from laparoscopic to robotic assisted radical prostatectomy: A single surgeon’s Australian regional centre experience - Basil Razi; Dane Cole-Clark; Duncan Self; Mark Louie-Johnsun (Continence Reports)
Introduction & Objectives:: Robotic assisted laparoscopic radical prostatectomy (RARP) is becoming standard of care for prostate cancer patients requiring surgical intervention. Postoperative continence significantly impacts patients’ quality of life, making functional outcomes a critical focus in the evolution of surgical techniques. Alternative methods, including open and laparoscopic techniques, have been superseded with increased availability of robotic units within Australia. This study aims to review an experienced laparoscopic surgeon’s transition to robotic prostatectomy and the impact on continence. Methods:: Prospective data collection included patient demographics, surgical method, and pad usage at 3 and 12 months postoperatively. The final 100 laparoscopic radical prostatectomy (LRP) cases (May 2019–August 2021) were compared with the first 100 RARP cases (August 2021–February 2023), all performed by the same surgeon. Continence rates were assessed using patient-reported pad usage. Results:: The mean age was similar between LRP (65.3 years) and RARP (65.4 years) groups. Continence rates at 3 and 12 months were 67.0% and 90.4% for LRP patients versus 78% and 94% for RARP patients. Odds ratio analysis indicated LRP patients were 1.75 and 1.66 times more likely to be incontinent at 3 and 12 months, respectively. Conclusion:: RARP demonstrated higher continence rates without evidence of a learning curve during the transition from LRP. These findings underscore the potential for improved patient outcomes with wider adoption of robotic systems in Australia.